Age-specific trends in limitations of daily activities in American adults aged 50–84 by race and ethnicity, 2000–2018 - Octavio Bramajo; Brandon O’Grady; Moumita Chakraborty; Neil K. Mehta (PLoS ONE, 2026)
During the first decade of the 2000s, disability levels began to stagnate or increase among American adults, a sharp departure from broad declines observed in earlier decades. It is unclear whether these adverse trends have continued after 2010, and whether there are variations by age group, sex, race/ethnicity, and nativity status. We used data from the 2000–2018 National Health Interview Survey to investigate trends in limitations of activities of daily living (ADL) and instrumental activities of daily living (IADL) by age group, race/ethnicity, and nativity among the 50 + population. We evaluated trends within the 2000–2009 and 2010–2018 periods. We find that adverse trends in disability documented in 2000–2009 continued into the 2010–2018 period, although the groups experiencing the largest increases shifted between decades. Middle-aged (50–64 years) adults displayed the most adverse trends compared to those ages 65–74 and 75–84, with some subgroups experiencing over 100% relative increases in ADL limitations. Disparities in disability by race/ethnicity widened considerably, with an alarming increase in disability among US-born Hispanics, particularly women at middle age, in the 2010–2018 period, while in the previous decade, Non-Hispanic Blacks and Non-Hispanic Whites presented the largest increases in IADL and ADL prevalence. Foreign-born Hispanics, who maintained the lowest disability levels through 2010, also experienced significant increases in the second decade. These trends provide an evidence base for understanding the direction of longer-term disability trajectories in the U.S. population and highlight the need for targeted prevention efforts among middle-aged adults and vulnerable demographic groups.